THE DISTRIBUTION OF PURULENT-INFLAMMATORY PROCESSES OF THE DISTAL EXTREMITIES OF COWS - Юрченко, І. І. (Scientific Progress & Innovations, 2014)
The results of monitoring studies on the distribution of purulent-inflammatory processes in the distal extremities of cows are presented in the article. Research conducted on the base of dairy farms of Poltava region in 2011-2013. We are proved that with free cow traffic, the finger papillomatosis dermatitis (56,5 %) has the largest share in the structure of pathology, while tethered content the superficial suppurative disease was most common (62,8 %). This data obtained show a significant spread of finger pathology and accordingly the harm that they give for the farms because of lower productivity.